AgPO2F2 and Ag9(PO2F2)14: the first Ag(i) and Ag(i)/Ag(ii) difluorophosphates with complex crystal structures. Issue 45 (22nd July 2015) - Malinowski, Przemysław J.; Kurzydłowski, Dominik; Grochala, Wojciech
Abstract : Detailed characterization is presented of novel AgPO2 F2 and AgI4AgII5(PO2 F2 )14 salts including their complex crystal structures and thermal decomposition. Abstract : The reaction of AgF2 with P2 O3 F4 yields a mixed valence Ag I /Ag II difluorophosphate salt with AgI4AgII5(PO2 F2 )14 stoichiometry – the first Ag(ii )–PO2 F2 system known. This highly moisture sensitive brown solid is thermally stable up to 120 °C, which points at further feasible extension of the chemistry of Ag(ii )–PO2 F2 systems. The crystal structure shows a very complex bonding pattern, comprising of polymeric AgII5(PO2 F2 )14 4− anions and two types of Ag I cations. One particular Ag II site present in the crystal structure of Ag9 (PO2 F2 )14 is the first known example of square pyramidal penta-coordinated Ag(ii ) in an oxo-ligand environment. Ag(i )PO2 F2 – the product of the thermal decomposition of Ag9 (PO2 F2 )14 – has also been characterized by thermal analysis, IR spectroscopy and X-ray powder diffraction. It has a complicated crystal structure as well, which consists of infinite 1D [Ag I O4/2 ] chains which are linked to more complex 3D structures via OPO bridges. The PO2 F2 − anions bind to cations in both compounds as bidentate oxo-ligands. The terminal F atoms tend to point inside the van der Waals cavities in the crystal structure of both compounds. All important structural details of both title compounds were corroborated by DFT calculations.